Preserving Indigenous Healing: Siddha Medicine as a Tool for Eco-tourism and Economic Revival in Northern Sri Lanka - Nithiakumar, N.; Sharsaayini, T.; Gumuthagini, V.; Sathiyaseelan, V. (Federation of Global Tamils, 2025)
Sri Lanka's three-decade civil war (1983-2009) devastated the Northern and Eastern provinces, wrecking infrastructure, livelihood, and culture. For this study, Siddha Medicine, an indigenous Tamil system, is explored as a vehicle for eco-tourism and livelihood restoration. Using a mixed- method research design 28 semi-structured stakeholder, wellness entrepreneur, and Siddha practitioner interviews, three focus groups, five site visits, and examination of 10 policy documents - conclusions highlight strong support for herbal products, healing trails, and integrative retreats from the community. SWOT analysis highlights cultural importance as strengths, weaknesses in infrastructure and market access, opportunities in eco-tourism, and over-harvesting threats.
Keywords: Cultural heritage; Eco-tourism; Post-war reconstruction; Siddha Medicine; Sustainable livelihoods